2019
DOI: 10.1111/asj.13277
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic profiles of the rumen microbiota during the transition period in low‐yield and high‐yield dairy cows

Abstract: We investigated potential relationships between rumen microbiota and milk production in dairy cows during the transition period. Twelve dairy cows were divided into a low‐yield (LY) or high‐yield (HY) group based on their milk yield. Rumen samples were taken from dairy cows at 3 weeks before parturition, and at 4, 8, and 12 weeks after parturition. 16S rDNA‐based metagenomic analysis showed that diversities of rumen microbiota in both groups were similar and the number of operational taxonomic units (OTUs) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Two bacterial taxa (i.e., Lachnospiraceae NK3A20 group—family Lachnospiraceae and Saccharofermentans —family Ruminococcaceae) were negatively correlated with growth performance in MA steers. This result is consistent with the observation of another study in which microorganisms assigned to the family Lachnospiraceae and to the genus Saccharofermentans were dominant in the rumen of dairy cows with low milk yields ( Sofyan et al, 2019 ). Despite the fact that Saccharofermentans and Lachnospiraceae spp.…”
Section: Discussionsupporting
confidence: 93%
“…Two bacterial taxa (i.e., Lachnospiraceae NK3A20 group—family Lachnospiraceae and Saccharofermentans —family Ruminococcaceae) were negatively correlated with growth performance in MA steers. This result is consistent with the observation of another study in which microorganisms assigned to the family Lachnospiraceae and to the genus Saccharofermentans were dominant in the rumen of dairy cows with low milk yields ( Sofyan et al, 2019 ). Despite the fact that Saccharofermentans and Lachnospiraceae spp.…”
Section: Discussionsupporting
confidence: 93%
“…Higher relative abundance of Anaerotruncus and Treponema, two potential cellulolytic bacteria [ 57 , 58 , 59 ], were observed in the MD group. In addition to the above genera, the relative abundance of Succinivibrio in the rumen has been reported to be positively associated with feed efficiency in beef cattle [ 60 ], and with milk production [ 61 ] and milk protein yield [ 62 ] in dairy cows due to its ability of produce succinate, the precursor of glucose. Although our results showed that MD contributed to a higher relative abundance of Succinivibrio in in vitro study, further animal studies are required to confirm whether MD plays a role in milk production or feed efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal tract microbiota of cows plays a vital role in the forage and other plant materials digestion, volatile fatty acid, and microbial crude protein production ( McCann et al, 2014 ). Additionally, previous studies have suggested that the gastrointestinal tract microbiota was associated with cows’ health ( Mao et al, 2012 ; Plaizier et al, 2017 ) and productivity traits, such as feed intake ( Li et al, 2020 ; Huang et al, 2021 ), milk production efficiency ( Shabat et al, 2016 ; Weimer et al, 2017 ), milk yield ( Indugu et al, 2017 ; Sofyan et al, 2019 ), and milk composition ( Xue et al, 2020 ; Wu et al, 2021 ). Therefore, the transition period is a major challenge for cows’ productivity and health, farm profitability, and animal welfare.…”
Section: Introductionmentioning
confidence: 99%